Abundance of Beneficial Soil Microbes in the Rhiosphere of Coffee Plants Infected by Pratylenchus coffeae - Reginawanti Hindersah; Iis Nur Asyiah (Biosaintifika: Journal of Biology & Biology Education, 2023)
Enzymatic transformation in the cycle of nutrients of Nitrogen (N) and phosphorus (P) in soil can only be carried out by microbes. The latest approach in coffee cultivation is to utilize soil microbes to enhance plant growth, also to reduce the attack of the nematode Pratylenchus coffeae on coffee roots. This exploratory study aimed to observe the attack of P. coffeae and the presence of N-fixing bacteria (NFB) and P- solubilizing microbes (PSM) in the coffee rhizosphere which in turn have the potential to be used as biological fertilizers and bioprotectants of coffee plants. The study was conducted in PT Perkebunan Kalibendo's Arabica and Robusta coffee fields, East Java, on immature plants (IP) and mature plants (MP). This exploration explained that the IP and MP arabica and robusta coffee plantations were attacked by P. coffeae. NFB and PSM were successfully isolated from the rhizosphere of both coffee plantations types. The population of NFB Azotobacter in IP was lower than in MP, but the PSM population in IP rhizosphere was not different from that in MP. Based on morphological and biochemical characterization, three isolates of Azotobacter bacteria, six species of P- solubilizing bacteria (PSB) and six species of phosphate-solubilizing fungi (PSF) were obtained. This exploration confirmed that the microbes involved in the N and P cycle colonized the coffee rhizosphere which was attacked by P. coffeae. Further research is recommended to observe the effectiveness of microbes as biological fertilizers and bioprotectants for coffee plants.